Análise ambiental de benzeno e hidrocarbonetos aromáticos policílicos por microextração em fase sólida e cromatografia gasosa acoplada à espectrometria de massas - Helvecio Costa Menezes (2011)
This work shows the development and validation of methods for quantification of benzene in ambient and exhaled air, polycyclic aromatic hydrocarbons in airborneparticulate matter, and naphthalene in ambient air. Solid phase microextraction was used for sampling and preconcentration, and a system for generating standard gaswith permeation tubes was used to the construction of calibration curves for benzene and naphthalene. The samples were analyzed by gas chromatography with mass spectrometry detector. A new cooling device was developed to sampling polycyclic aromatic hydrocarbons for there extraction from airborne particulate matter by cold fiber solid phase microextraction. The validated methodologies were applied to theanalysis of real samples in ambient air of parks, streets, offices, laboratories and fuel stations at the city of Belo Horizonte. In addition, analyses of benzene in exhaled air of occupationally exposed individuals were performed simultaneously. The analysis of polycyclic aromatic hydrocarbons were made into particulate matter collected atthe city of Divinópolis over a period of six months. The methods developed in this study show to be suitable to environmental analysis for the determination of benzene in ambient and exhaled air, naphthalene in the environment, and PAH in airborne particulate matter. The results showed significant correlations between the concentrations of benzene in ambient and exhaled air of subjects occupationally exposed to benzene. The new method proposed for the determination of PAH is sensitive, fast and furthermore dispense the use of toxic solvents. The technique ofcold fiber solid phase microextraction can be applied to other analyses including food, water, soil, plants and biological fluids